Pediatric Spinal Cord Contusion: A Case Report Highlighting Clinical Symptoms and Management Strategies in a 2-Year-Old Patient - Chriswidarma, Dewa Gede; Adityawarma, Anak Agung Ngurah Agung Harawikrama; Lauren, Christopher; Satyarsa, Agung Bagus Sista; Suarjaya, I Putu Pramana; Mahadewa, Tjokorda Gde Bagus (https://snacc.org/wp-content/uploads/2019/fall/Intl-news3.html, 2025)
Spinal cord injuries (SCI) can be resulted in permanent disability, often caused by high-intensity incidents such as car accidents, falls, and violent crimes. Although relatively rare in children, they can have profound effects. This case report was aimed to elucidate the clinical symptoms of Th1-Th3 spinal contusion in a 2-year-old patient. A 2-year-old boy presented to a private peripheral hospital with complaints of back pain following a traffic accident. The examination revealed complete motor weakness (0/5) in both lower extremities, with preserved sacral sparing. Thoracolumbar MRI demonstrated spinal cord contusion and edema at the level of Th1-Th3. Based on history, physical examination, and supporting tests, the patient was diagnosed with SCI ASIA Impairment Scale B and upper thoracic spinal cord contusion, leading to the decision to perform laminectomy at the Th2-Th3 level. This case underscores the importance of recognizing initial symptoms in spinal cord injury cases and being vigilant for red flags in spinal trauma cases. Prompt initial trauma treatment, such as patient immobilization, is crucial. In this instance, laminectomy decompression was undertaken to address the contusion. A high level of vigilance was required as neurological symptoms could evolve or be initially obscured. Spinal cord injuries often manifest within days of an accident, although they can remain undetected for extended periods. Cord contusions may present with neurological symptoms, necessitating prompt diagnosis via spinal magnetic resonance imaging (MRI) and potential emergency surgical intervention, such as laminectomy.